USE OF GENETIC MARKERS TO AID CONSERVATION DECISIONS FOR GROUPS OF RARE DOMESTIC BREEDS - Piyasatian, N; Kinghorn, B.P. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2007)
An approach to balancing genetic diversity and genetic merit in animal conservation programs is presented and illustrated by simulated example. Microsatellite markers are used to characterise the genetic variation among animals selected to join a conservation program. This is done by consideration of genetic variation within and between breeds at the marker loci. Perceived mean merit of the breeds is also considered. A weighting factor balancing diversity and merit is varied to give a range of possible outcomes. The resulting frontier of diversity and merit combinations is characteristic of the total animal resource, measurements made on it, and the size of the conservation program. It is suggested that practitioners choose an appropriate solution from this frontier. Extension of the method seems possible to help make decisions on factors such as rationalising breeds via crossbreeding and investment in conservation facilities. Keywords: Genetic markers, genetic conservation, endangered breed, differential evolution Corresponding author: E-mail: napapan.piyasatian@gmail.com